Description of a new surgical approach for elbow arthroplasty: Selective Triceps-On Medial Paraolecranon (STOMP) approach - Carlos Prada, MD; Sirat Khan, MBBS, PhD; Thomas Goetz, MD; Bashar Alolabi, MD, MSc (JSES International)
Background: Surgical approaches for total elbow arthroplasty (TEA) are broadly divided into two groups; “triceps-off” and “triceps-on” approaches. Traditional “triceps-off” approaches provide excellent visualization for TEA; however, they carry a risk of triceps failure and require triceps protecting rehabilitation protocols. Triceps-on approaches have the advantage of preservation of triceps function yet present technical challenges for access to and preparation of the bony surfaces of the proximal ulna and radius. We present here the operative technique, indications, and initial outcomes of a novel Selective Triceps-On Medial Paraolecranon (STOMP) approach for TEA, which allows both preservation of the triceps function and excellent exposure to the proximal ulna with minimal risk to the ulnar nerve. Methods: A two center, retrospective cohort study of all patients undergoing primary TEA, hemiarthroplasty, or revision elbow arthroplasties using the STOMP approach in the practice of the senior authors between 2010 and 2020 were reviewed. Patient data, including admission demographics and diagnoses were collated. Outcome measures were collected from patient charts. Results: A total of 37 elbow arthroplasties in 35 patients were performed with the STOMP approach during the reviewed period, of which 27 patients (77%) were female. Thirty-two arthroplasties were primary cases (86%), and 5 (14%) were revision cases. The main indications leading to elbow arthroplasty was rheumatoid arthritis (n = 18, 49%) followed by primary or secondary elbow osteoarthritis (n = 9, 24%) and distal humeral fracture (n = 7, 19%). There were 7 postoperative complications (19%). Five patients (14%) developed elbow stiffness, one patient a postoperative olecranon fracture (n = 1, 3%) and one patient had an ulnar nerve injury with incomplete resolution but that did not warrant surgical treatment (n = 1, 3%). A reoperation was required in 3 patients (9%). Conclusion: The STOMP approach is a safe approach for elbow arthroplasty surgery. It does not detach the triceps and we believe it offers improved exposure and safety compared to other triceps-on techniques. Furthermore, this approach allows excellent surgical access to the coronoid, olecranon, and ulnar canal with low midterm complications.